2022
DOI: 10.1002/mp.15823
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of dosimetric impact against position errors in accelerator‐based BNCT under different treatment parameter settings

Abstract: Background Patients who undergo accelerator‐based (AB) boron neutron capture therapy (BNCT) for head and neck cancer in the sitting position are generally uncomfortably immobilized, and patient motion during this treatment may be greater than that in other radiotherapy techniques. Furthermore, the treatment time of BNCT is relatively long (up to approximately 1 h), which increases the possibility of patient movement during treatment. As most BNCT irradiations are performed in a single fraction, the dosimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study of Lee [7] showed the mean dose of deep-seated tumor changes by 1% and 5% for lateral and outward shifts from the source plane, respectively, while the mean dose of superficial tumor without significant variation by 1 cm shift or 15˚ tilt. The research of Kakino [8] illustrated a significant reduction of tumor dose due to increased distance from the collimator, and the smaller the collimator, the more severe the tumor dose reduction. However, they considered a cylindrical phantom to investigate the effect of placement deviation on dose distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Lee [7] showed the mean dose of deep-seated tumor changes by 1% and 5% for lateral and outward shifts from the source plane, respectively, while the mean dose of superficial tumor without significant variation by 1 cm shift or 15˚ tilt. The research of Kakino [8] illustrated a significant reduction of tumor dose due to increased distance from the collimator, and the smaller the collimator, the more severe the tumor dose reduction. However, they considered a cylindrical phantom to investigate the effect of placement deviation on dose distribution.…”
Section: Introductionmentioning
confidence: 99%